Mediación policial y tutela judicial efectiva en la actualidad: reflexiones de una romanista - Guillamón, Carmen Lázaro (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
It is not disputed that the right to effective judicial protection is the key in shaping the State of Law, but it has also impeded the possibility of establishing forms of extrajudicial justice, which are considered a salvation for a “sick” justice system. The study of this issue requires a historical analysis of the Roman law, which will produce a historical framework for presenting the activity of the Police as a conflict manager from a dogmatic point of view. Thus, the importance of and the work of praetors – jurisdiccional magistrate- will be highlighted, not only as historical antecedents, but as essential elements in the configuration of the Justice Administration System in which mediation has to be included as one of its instruments.